Mengintegrasikan Praktik Sufi Dalam Pendidikan: Kerangka Strategis Untuk Mengembangkan Karakter Religius Pada Siswa - Sodikin (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
Religion is the primary foundation for character formation. However, religious values have not yet fully integrated into the students’ psyche. This research explores the development of religious character by integrating Sufi practices in education. The study was conducted at an Islamic boarding school, Aliyah madrasah, in Malang. The findings indicate that integrating Sufi practices into the educational curriculum significantly impacts the development of religious character. The strategy begins with the preparation of a clear vision and mission, an integrated curriculum, and the presence of teacher role models, all of which are crucial for fostering religious character. A conducive environment, regular evaluations, and religious extracurricular programs are also essential. In conclusion, a comprehensive educational process emphasizing responsibility, obedience, regular evaluations, religious extracurricular programs, partnerships with families and communities, and spiritual strengthening activities can effectively enhance students' religiosity.